Teknik Penulisan Bahasa Dalam Karya Tulis Ilmiah - tri karyanti (Universitas Aki, 2014)
Language Writing Techniques in scientific papers which include the application of spelling, grammar, and traditions are commonly used in scientific writing. Application of standards Spelling should conform with Enhanced Indonesian. Grammar must obey the principles applied in the field of science that is accurate, brief, and clear. When the message contained in the sentence reaches the reader, the choice of words should pay attention to the existence of (1) accuracy, (2) standardness, (3) effectiveness, (4) and the subtlety of meaning. Key Words: Scientific Writing, spelling, grammar